Fabrication of mesoporous Co3O4 oxides by acid treatment and their catalytic performances for toluene oxidation - Li, Genqin; Zhang, Chuanhui; Wang, Zhong; Huang, He; Peng, Hui; Li, Xuebing (Applied catalysis. A, General, 2018)
[Display omitted] •Mesoporous Co3O4 was prepared by precipitation with subsequent acid treatment.•The diluted acid treatment significantly enhanced the catalytic activity of Co3O4.•The specific surface area plays a vital role in the reaction.•Surface acidity, Co2+/Co3+ and Oads species were also key parameters in the reaction. Considering the harmful effects of volatile organic compounds (VOCs) on the atmosphere and public health, the search for proper catalytic materials for the effective catalytic elimination of VOCs remains one of the most pressing issues in the environmental field. In this study, a series of mesoporous Co3O4-n (n=0.00, 0.0001, 0.01, 0.05, 0.10, 1.00, representing the concentration of HNO3 aqueous solution) catalysts were fabricated by the acid treatment of Co3O4 that was previously prepared via a hydroxycarbonate precipitation method (Co3O4-P). The catalytic performances of the prepared catalysts were evaluated for the model reaction of toluene oxidation. An obvious enhancement of catalytic activity in the reaction was achieved over the acid-treated Co3O4 catalysts using lower HNO3 concentrations, with Co3O4-0.01 exhibiting the optimum catalytic activity (T90=225°C, 15°C lower than that of Co3O4-P), excellent catalytic durability under dry conditions and a high regeneration capability under humid conditions. Benefitting from the dilute acid treatment, the Co3O4-n (n=0.01, 0.05, 0.10) catalysts presented higher specific surface areas, more weak acidic sites and higher abundances of surface Co2+ and Oads species, which were regarded as the key factors responsible for their enhanced catalytic activities.